PENGARUH RASIO KEUANGAN DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PERUSAHAAN PROPERTY DAN REAL ESTATE - Nurtazkia, Putri Abrilla; Eriswanto, Elan (COMPETITIVE, 2023)
This study aims to determine Influence of Financial Ratios and Dividend Policy On Stock Prices of Property and Real Estate Companies listed on the IDX for the 2015-2019 period. This type of research is quantitative associative. By using the independent variables include the Current Ratio, Return On Equity and Dividend Payout Ratio while the dependent variable includes Stock Prices. This population of this research is Property and Real Estate companies for the 2015-2019 period. The research sample consisted of 15 Property and Real Estate companies for the 2015-2019 period. The data analysis technique used classical assumption test, t test, F test, multiple linear regression analysis and the coefficient of determination. The results of this study state that partially Current Ratio and Dividend Payout Ratio have no positive influence on stock prices, while Return On Equity has a positive influence on Stock Prices. If simultaneously Current Ratio, Return On Equity and Dividend Payout Ratio have a positive influence on Stock Prices.